363 FOUNDATIONS OF CLINICAL MEDICINE COURSE LINKED TO IMPROVED NATIONAL BOARD OF MEDICAL EXAMINERS STEP 2 SCORES. Issue 1 (1st January 2007) - Brownfield, E. L.; Blue, A. V.; Powell, C.; Geesey, M. E.; Moran, W.
Abstract : Purpose: Although American medical schools have revised their curriculum over the past two decates, there have been few successful examples of the reintroduction of the basic sciences during the clinical years. Foundations of Clinical Medicine (FCM) at the Medical University of South Carolina was developed as a third-year course with the goal of integrating the basic and clinical sciences in a clinically relevant fashion while simultaneously fostering students' continued self-directed learning and reasoning skills. Methods: All required third-year clerkship students participated, with the exception of family medicine students, who spent a substantial portion of their time off campus. FCM was introduced at the beginning of the 2001-2002 academic year, and over the subsequent years, the clerkship rotations remained substantially the same, although some clerkships reduced the number of faculty lecture hours and substituted FCM course material. Students were divided into small groups (8-12) on each clerkship and assigned to a specialty-specific preceptor for each rotation with whom they generally met for 60 to 90 minutes once per week. A syllabus was distributed with learning goals, references, and clerkship-specific clinical cases. Discussion areas, including basic science and clinical topics, were included for each case. Composite class scores for the National Board of Medical Examiners Step 2 CK test were compared to step 1 results in the classes before and after the implementation of FCM. Results: For the three classes before FCM was implemented (1999-2001) the mean step 2 score (207.7, n = 382) was significantly lower than for the three classes (2002-2004) after the FCM implementation (215.9, N = 361) ( p < .0001). Although mean step 1 scores were also lower for the pre-FCM classes (205.4 vs 210.5, p = .04), an analysis of variance model incorporating test group, step 1 score, race, gender, and student age confirmed that the post-FCM group scored significantly higher than the pre-FCM group. The test group parameter estimate was 4.02 ( p < .001). In this model, the step 1 score was also a significant predictor of step 2 score: parameter estimate 0.699 ( p < .001). The model's adjusted R 2 was 0.5375. Conclusions: Both step 1 scores and the FCM course were independent and significant predictors of step 2 performance for medical students. A centrally developed curriculum integrating clinical and basic sciences is feasible for the third year of medical school and is associated with an improvement in standardized testing.